Model for implementing sustainable agriculture based on good agricultural practice as a strategy for adapting to the impact of climate change - Prajanti, Sucihatiningsih Dian Wisika; Litaay, Christina; Widiatningrum, Talitha; Amelia, Dhea Rizky; Adzim, Fauzul (Edelweiss Applied Science and Technology, 2025)
The aim of this research is to develop a strategy for implementing sustainable agriculture based on good agricultural practice as a strategy for adapting to the impacts of climate change. This research was conducted in the Kopeng area, Semarang Regency, Central Java, which is one of the areas in Indonesia that is rich in agricultural potential. Efforts to implement a sustainable agricultural model in Kopeng Village considering that the majority of agriculture in this area still relies on conventional agricultural techniques which have an impact on reducing land quality. The data analysis method used in this research is ANP (Analytic Network Process) which is a mathematical theory that allows decision making to deal with interrelated factors (dependence) as well as mathematical feedback. The results of the research show that the Sustainable Agriculture Implementation Model Based on Good Agricultural Practice as a Strategy for Adapting to the Impact of Climate Change in Kopeng Village requires attention to six criteria, including sustainable land management, efficient use of water, conservation of biodiversity, reduced use of chemicals, increased welfare farmer socio-economics, climate change adaptation and mitigation. The most prioritized criterion is sustainable land management. In the criteria for sustainable land management, there are three sub-criteria, including Crop Rotation, No-till land management and Use of land cover. Of the three sub-criteria, the sub-criteria that is most prioritized in the criteria for sustainable land management is crop rotation.